Multidisciplinary strategies to reduce radiotherapy-induced cardiotoxicity in breast cancer: surgical and technological innovations - Lu, Kai; Sun, Zhenhua; Yi, Yide (Frontiers in Oncology, 2025)
Radiotherapy remains essential in breast cancer management, yet its long-term cardiotoxicity, driven primarily by radiation-induced myocardial fibrosis, threatens survivorship, particularly in left-sided tumors. Surgical refinements, including breast-conserving surgery with sentinel lymph node biopsy and total mastectomy, effectively reduce radiation fields and cardiac exposure. Intraoperative radiotherapy with lead shielding markedly lowers left anterior descending artery dose from 5.2 Gy to 0.07 Gy. Technological advances—such as deep-inhalation breath-hold, proton therapy exploiting the Bragg peak, and intensity-modulated radiotherapy, further optimize cardiac sparing while preserving oncologic efficacy. Integrating intraoperative image guidance, pharmacological cardioprotection, and AI-assisted planning facilitates precise dose delivery tailored to individual anatomy and risk. This review synthesizes multidisciplinary strategies to mitigate cardiac injury through surgical and technological innovation, underscoring a paradigm shift toward organ-sparing precision radiotherapy. Future directions include the application of degradable shielding materials, senescence-targeted therapies, and predictive modeling to balance therapeutic efficacy with long-term cardiovascular safety in breast cancer care.